2019
DOI: 10.3390/ijms21010299
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature-Dependent Retention of Introns in GPI8 Transcripts Contributes to a Drooping and Fragile Shoot Phenotype in Rice

Abstract: Attachment of glycosylphosphatidylinositols (GPIs) to the C-termini of proteins is one of the most common posttranslational modifications in eukaryotic cells. GPI8/PIG-K is the catalytic subunit of the GPI transamidase complex catalyzing the transfer en bloc GPI to proteins. In this study, a T-DNA insertional mutant of rice with temperature-dependent drooping and fragile (df) shoots phenotype was isolated. The insertion site of the T-DNA fragment was 879 bp downstream of the stop codon of the OsGPI8 gene, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 53 publications
4
25
0
Order By: Relevance
“…Overall, a moderate divergence among sequences was demonstrated, compared to several genera recently reported 44 , 61 , 68 – 70 . Of note, petA-psbJ-psbL , the most divergent region revealed in the present study, has also been demonstrated to be highly divergent in many genera 68 , 69 , 71 , 72 . Even though high diversity was observed in trnH-psbA and ycf1 , which have extensively suggested to be taken as universal barcodes 73 and depicted has a capacity for sufficient variation information for taxon discrimination in angiosperms 72 , 74 , no one hotspot alone was enough to distinguish these seven herbs.…”
Section: Discussionsupporting
confidence: 70%
“…Overall, a moderate divergence among sequences was demonstrated, compared to several genera recently reported 44 , 61 , 68 – 70 . Of note, petA-psbJ-psbL , the most divergent region revealed in the present study, has also been demonstrated to be highly divergent in many genera 68 , 69 , 71 , 72 . Even though high diversity was observed in trnH-psbA and ycf1 , which have extensively suggested to be taken as universal barcodes 73 and depicted has a capacity for sufficient variation information for taxon discrimination in angiosperms 72 , 74 , no one hotspot alone was enough to distinguish these seven herbs.…”
Section: Discussionsupporting
confidence: 70%
“…The principal mechanism of cisplatin cytotoxicity is the formation of platinum–DNA adducts. Thus cellular mechanisms leading to a reduction in cisplatin-induced DNA damage are key factors in the development of cisplatin resistance 41 . The majority of cisplatin-induced DNA lesions, intra-strand adducts, and inter-strand crosslinks are removed by nucleotide excision repair.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the bulk of cisplatin is actively moved in and out of the cell by copper transporters (CTR1, ATP7A and ATP7B) 44 . Nonetheless, the following ATP-binding cassette (ABC) ATPase genes ABCG2, ABCC2, ABCA1 , and ABCC1 have been associated with cisplatin resistance in diverse cancers 41 , 44 47 Thus, we investigated the mRNA expression levels of CTR1 , ATP7A , ATP7B , ABCG2, ABCC2, ABCA1 , and ABCC1 after exposure to e-cigarette extracts alone without cisplatin. Following 48 h of e-cigarette exposure, we observed that the expression of the copper transporter CTR1 , which mediates the uptake of cisplatin, was down-regulated at the mRNA level in WSU-HN6 for all e-cigarette extracts tested, but remained unchanged in the other cell lines (Figure S3 a).…”
Section: Resultsmentioning
confidence: 99%
“…Since the development of CDDP in the 1970s, this platinum-based chemotherapy drug has shown promising anticancer efficacy in a variety of cancers, including NPC. In addition to monotherapy, combination treatment with CDDP and other anticancer therapies, such as radiotherapy and other chemotherapy drugs, is also a common therapeutic strategy in cancer patients because of its synergistic effect against tumor growth [ 8 , 9 ]. Even with the advances in immunotherapy, combination treatment with CDDP and an immune checkpoint inhibitor has demonstrated survival benefits in patients with a certain type of cancer, including head and neck cancer [ 8 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDDP, a platinum-based anticancer agent, is effective against several types of human cancers [ 8 , 9 ]. In general, CDDP can induce apoptotic cell death through platinum–DNA adduct formation.…”
Section: Introductionmentioning
confidence: 99%